VACUUM REDUCTION OF SAPROLITE NICKEL ORE USING VARIOUS REDUCING AGENT AND CAO AS ADDITIVE AT 1200 C AND 1400 C - Fadisya, Azzahra
Nickel plays a significant role in world development due to its superior physical and chemical properties. Nickel can be extracted from two types of ores, namely lateritic and sulphide ores. The most widely used method for lateritic nickel ore processing, especially the saprolite type, is the rotary kiln-electric furnace (RKEF) process. The process produces ferronickel and smelting slag which are still rich in magnesium. This fact along with the increasing demand for magnesium and nickel drives research to utilize magnesium contained in ferronickel smelting slag and in the initial ore as well by simultaneously reduce MgO with reduction of nickel and iron oxides. This research studied the effects of reduction temperature, types of reductants, and addition of CaO on the vacuum reduction process of saprolite nickel ore. Experimental procedure began with preparation and characterization of the materials used, such as saprolite nickel ore, ferrosilicon, aluminum powder, coal, CaO, and CaF2. Saprolite nickel ore and CaO are calcined before being mixed with CaF2 as catalyst and ferrosilicon, aluminum powder, or coal as reducing agents and then briquetted. The vacuum reduction process was carried out using a box type vacuum furnace with a non-isothermal temperature method with an initial temperature of 25°C, increased gradually to 1200°C and 1400°C and then held for 4 hours and cooled down gradually to room temperature. The vacuum reduction process was carried out by varying the types of reducing agents, namely ferrosilicon, aluminum powder, and coal, as well as the mass ratio of saprolite nickel ore to CaO of 25%:75%, 50%:50%, 75%:25%, and without CaO. Experiment result shows that increasing the reduction temperature increases saprolite nickel ore reduction rate and evaporation of magnesium. Samples reduced by coal produce the greatest change in weight compared to other reductants which is most likely due to the evaporation of the volatile matter content in the coal. Increasing the addition of CaO to the sample with ferrosilicon and aluminum reducing agents increases the change in sample weight. The experimental results indicate that the calcium tends to displace magnesium from its bonds with other elements in a phase, thereby facilitating the reduction and evaporation processes. This is also supported by the presence of calcium-rich phases which contain relatively fewer magnesium such as dicalcium ferrite, dicalcium silicate, monoxide with high calcium content, (Ca,Mg)2(Fe,Al)2O5, and (CaO,FeO)12( Al2O3)7. Experimental results also indicate that aluminum reducers tend to produce more reductive conditions than other types of reducing agents when viewed based on their ability to reduce iron oxide.